Description Of Nutritional Status In Students Mts Al-Amin Pakis - Sholehudin, Achmad; Kusmawati, Wiwik (JUPE : Jurnal Pendidikan Mandala, 2024)
Adolescents are an age group that is vulnerable to experiencing malnutrition or excess nutrition problems. Teenagers generally carry out higher physical activity compared to other ages, so they require more nutritional fulfillment. However, the incidence of overnutrition in adolescents can also occur due to poor eating habits so that the amount of energy input is greater than the energy expended. The purpose of this study was to describe the nutritional status of students. This type of research is quantitative with an analytical descriptive design on 85 students of MTs Al-Amin Pakis. Data on nutritional status were obtained by measuring the height using a microtoise and the respondent's weight using a mechanical scale. Nutritional status is classified based on the value of the BMI/age z-score table for children aged 5-18 years from the 2011 Indonesian Ministry of Health guidelines. The results of the data analysis obtained the nutritional status category of junior high school students who were involved as the majority of respondents who were in the normal nutritional status category, namely 77 people (90.58%). However, there were still 8 students (9.41%) who were obese.